A distal (type 1) renal tubular acidosis case that mimic coronary ischemia. (1st August 2013) - Tekçe, Hikmet; Aktaş, Gülali; Öztürk, Serkan
Abstract: Introduction : Type 1 (distal) renal tubular acidosis (RTA) is a rare clinical condition characterized with defect of urinary acidification in distal tubulus. If diagnosis delays, RTA may cause metabolic and clinical complications and comorbidities. We describe here a type 1 distal RTA case with symptoms mimicking coronary ischemia. Case report : A 46-year-old woman admitted with complaints of chest pain, palpitation, walking disability, fatigue and nausea. On physical examination muscles were weaken 3/5 in four extremities. An electrocardiogram revealed supraventricular tachycardia and ST depression on precordial V2-6 derivations. An acute coronary syndrome diagnosis made based on anginal symptoms, supraventricular tachycardia, ST depression on V2-6 derivations and elevated cardiac enzymes. Urgent coronary angiography was normal except a 30% narrowing in LAD. She had recurrent nephrolithiasis and had operated because of hydronephrosis. She had two episodes of fatigue and walking disability previously. Hyperchloremic metabolic acidosis with normal anion gap determined in blood gas analyze. Patient diagnosed with type I RTA with the signs and symptoms of recurrent nephrolithiasis, fatigue, severe hypokalemia (1.8 mmol/L), hyperchloremic metabolic acidosis with normal anionic gap, alkaline urine (pH 8) and positive urinary anionic gap (13.7 mmol/L). Sodium bicarbonate infusion and potassium replacement therapy administered. Clinical and laboratory signs of the patient dissolved during treatment. Conclusion : Type 1 RTA should be considered in acidotic patients admitted with hypokalemia and coronary symptoms. Urinary and blood gas analyses should be done beside cardiac tests initially. Therefore, a precise diagnosis may be possible without the possible complications of unnecessary coronary interventions.